Cross-reactivity of human and a putative pig IgD. Pig IgD-like molecules as serum and lymphocyte components - Zikán, J; Síma, P; Tucková, L (Folia microbiologica, 1983)
Proteins of pig serum and splenocytes which were isolated on immobilized guinea pig antibodies against human IgD were characterized by SDS-PAGE. In both cases the main isolated components possessed several properties nearly identical with those of human IgD: molar mass of the components and their chains, and susceptibility of the heavy chains, light chains, the chymotryptic peptide maps of the chains, and susceptibility of the heavy chains, the chymotryptic peptide maps of the chains, and susceptibility of the heavy chains in the native molecule to trypsin digestion. These IgD-like components not adsorbed on immobilized normal guinea-pig IgG. We suggest that the components of pig serum and splenocytes cross-reacting with highly specific antibodies against human IgD represent candidates for pig IgD. The percentage of the IgD-like molecules on the surface of pig splenocytes labeled with the antibody against human IgD was similar to the percentage of splenocytes bearing all immunoglobulins. Therefore, we suggest that IgD-like molecules were occurring on the surface of cells mostly together with molecules of another immunoglobulin class.
Keywords: Electrophoresis, Polyacrylamide Gel; zkřížené reakce; Humans; Immunoglobulin D; druhová specificita; elektroforéza v polyakrylamidovém gelu; Lymphocytes; lymfocyty; lidé; Cross Reactions; zvířata; imunoglobulin D; Swine; Spleen; Species Specificity; Myeloma Proteins; Animals; myelomové proteiny; prasata; slezina